Contribuição para discussões sobre questões ambientais relacionadas aos bens da natureza - Rocha, Eremilda Silveira (2015)
The subject of the study is the environment, approached more from the social point of view, with one general focus conventionally called goods of the nature. The adopted premise is that nature can only be measured as good when implicit values categories. These categories only occur in our political system and change through time, also changing the concepts, for example, the environment, a strong word that passes all over this work. The first questions are exactly those ones related to this word, environment, which has taking various focuses in the last years, due to the necessity of the political systems include in their agendas questions directed to regulate the uses of the so called goods of the environment. Why this occurred in our country? Why, in general, a political system is forced to include in their agenda programs that normally would have no attention? These questions compose a general vision of the study problem I did.I adopted in the work two points in order to answer these questions: on normative vision, which presents the problem from the oversight point of view, and a more humanistic vision looked through the eyes of the man-nature relationships. The adopted hypotheses, in the sense of provisory answers to the questions, were: i) in the absence of specific concepts, the system used the already existing concepts of economic goods, public and private, ii) from the humanistic point of view, which includes in its center the relations man-nature, it is difficult categorize the nature as a good in the economic sense, iii) the dominant political system use its ideological armory in order to establish the so called environmental services, but there are various questions related to this approach. I verified the adopted hypothesis through the current literature and published reports as examples; therefore I did not direct verifications, but general interpretations with basis in history and reports. In Results it is presented the concepts involving the questions under the normative points of view and in Discussion the same normative aspects are presented under the analytic view, establishing the contradictions with more details. It is briefly presented in the Discussion how these questions are involved in Roraima and presented some suggestions of how to approach this theme in the region.